Jejunal diaphragm disease associated with cytomegalovirus infection - Kagebayashi, Sumika; Yamamoto, Shuji; Seno, Hiroshi (Endoscopy International Open, 2019)
Background and study aims Diaphragm disease (DD) is a rare gastrointestinal disease featuring multiple thin, circumferential strictures in the intestine, related to prolonged intake of nonsteroidal anti-inflammatory drugs (NSAIDs). Here, we report a case of DD associated with cytomegalovirus (CMV) infection in a patient not taking NSAIDs. A 72-year-old man was referred to our hospital due to persistent epigastric pain. Push enteroscopy showed extensive mucosal detachment in the upper jejunum. Immunohistochemistry examination of biopsy specimens revealed CMV positivity. In addition, CMV antigenemia was positive. Antiviral treatment with ganciclovir improved his symptoms and the CMV antigenemia became negative. Wireless capsule enteroscopy performed 1 month after antiviral treatment showed regenerated mucosa and multiple diaphragm-like strictures in the jejunum, resulting in capsule retention. Balloon dilatation using double balloon enteroscopy (DBE) was performed and the capsule was retrieved endoscopically. DBE 6 months after antiviral therapy confirmed no recurrence of stenosis or inflammation. The patient had no history of long-term NSAID use. In a case of DD unassociated with NSAIDs, CMV infection should be considered in the differential diagnosis.